ANTIOXIDANT PROPERTIES OF GYNURA PROCUMBENS EXTRACTS AND THEIR INHIBITORY EFFECTS ON TWO MAJOR HUMAN RECOMBINANT CYTOCHROME P450S USING A HIGH THROUGHPUT LUMINESCENCE ASSAY. - Afandi, Atiqah; Zulkiffli M, Halimhilmi; Sadikun, Amirin; Ismail, Sabariah (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objective: Gynura procumbens is an evergreen herb traditionally used to treat various diseases such as fever, kidney disease, and diabetes. Despite various studies conducted on the pharmacological activities of G. procumbens, the interaction between this herb with drug-metabolizing enzymes is still unknown. Methods: This study investigates the effects of ethanol, methanol, and aqueous extracts of G. procumbens on CYP3A4 and CYP1A2 enzyme activities along with its antioxidant capacity using high throughput luminescence assay. Results: The content of phenolic compounds in G. procumbens extracts can be ranked in decreasing order as follows: Methanol extract > ethanol extract > aqueous extract, whereas the content of flavonoid compounds in G. procumbens extracts can be ranked in decreasing order as follows: Ethanol extract > methanol extract > aqueous extract. The methanol extract of G. procumbens exhibited the most active free radical scavenger compared to the other extracts. Ethanol extract of the G. procumbens exhibited strong inhibitory effect on CYP3A4 and CYP1A2 enzyme with IC50 values of 32.01Â±1.11 Î¼g/mL and 7.87Â±1.22 Î¼g/mL, respectively. The methanol extract exhibited weak inhibitory effect on CYP3A4 and CYP1A2 enzymes with IC50 values more than 100 Î¼g/mL. The aqueous extract, on the other hand, demonstrated no inhibitory effect on both enzymes. Conclusion: The inhibition of CYP3A4 and CYP1A2 in this study follows the rank order of total flavonoid content (ethanol extract > methanol extract > aqueous extract) in which the higher the total flavonoid content in the extract, the higher would be the inhibition of drug metabolizing enzymes studied. Keywords: Gynura procumbens, Antioxidant properties, CYP3A4, CYP1A2.